Nasal airflow patterns in a patient with septal deviation and comparison with a healthy nasal cavity using computational fluid dynamics - Corda, John Valerian; Shenoy, B. Satish; Lewis, Leslie; K., Prakashini; Khader, S. M. Abdul; Ahmad, Kamarul Arifin; Zuber, Mohammad (Frontiers in Mechanical Engineering, 2022)
Background and Objective: Causes for nasal airway obstruction (NAO) are many but septum deviation is the most prevalent etiology. A deviated septum affects the airflow dynamics in the human nasal cavity, which in turn affects the physiological functions of the nasal cavity like heating, humidification and filtration capabilities. The present study investigates and compares the airflow patterns in a healthy nasal cavity to a septal deviated nasal cavity. Methods: Two nasal airway models are considered and compared in this study.One with a septal deviation and the second with a healthy patent nasal cavity. Airflow analysis is carried out by developing the CT scans into 3D models using Materialise MIMICS (Materialise, Ann Arbor, MI), and then using FLUENT solver of ANSYS 2020R2. The simulations are carried out for airflows ranging in laminar and turbulent flows using the SST k- turbulence model. Polyhedral mesh is used and the mesh check using Grid Convergence Index studies is adopted. Results: The pressure and velocity profiles are assessed for a wide range of mass flow rates. The results indicate a turbulent flow pattern for mass flow rates over 15 LPM. The velocity profiles show aberrated flow profiles in a septal deviated nasal cavity where the peak velocity is observed at the mid nasal region rather than the nasal valve region. There was a 38 % to 55% higher nasal resistance in the septal deviated nasal cavity as compared to a normal and healthy nasal cavity. The pressure drop in the septal deviated nasal cavity is higher by 60% to 120% when compared to a healthy nasal cavity. Conclusions: The septal deviated nasal cavity greatly affects the nasal airflow distribution resulting in higher velocities in the mid nasal region, increased pressure drop and higher nasal resistance. Hence the NAO with septal deviation has to be rectified with proper surgical procedures.